2018
DOI: 10.1155/2018/5783976
|View full text |Cite
|
Sign up to set email alerts
|

Multibiometric Fusion Authentication in Wireless Multimedia Environment Using Dynamic Bayesian Method

Abstract: Single biometric method has been widely used in the field of wireless multimedia authentication. However, it is vulnerable to spoofing and limited accuracy. To tackle this challenge, in this paper, we propose a multimodal fusion method for fingerprint and voiceprint by using a dynamic Bayesian method, which takes full advantage of the feature specificity extracted by a single biometrics project and authenticates users at the decision-making level. We demonstrate that this method can be extended to more modal b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…In 2017, Moi and Pang proposed a multibiometric authentication framework that combines the iris and human face 11 . In 2018, Wu et al proposed a fingerprint and voice print fusion authentication framework that is based on the dynamic Bayes 12 . In 2020, Gupta et al proposed a new revocable multimodal biometric identification system 13 .…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2017, Moi and Pang proposed a multibiometric authentication framework that combines the iris and human face 11 . In 2018, Wu et al proposed a fingerprint and voice print fusion authentication framework that is based on the dynamic Bayes 12 . In 2020, Gupta et al proposed a new revocable multimodal biometric identification system 13 .…”
Section: Related Workmentioning
confidence: 99%
“…11 In 2018, Wu et al proposed a fingerprint and voice print fusion authentication framework that is based on the dynamic Bayes. 12 In 2020, Gupta et al proposed a new revocable multimodal biometric identification system. 13 By projecting feature points onto a random plane to generate revocable features, this system can achieve a better privacy protection performance by integrating multimodal feature data.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…They also proposed a three‐bit quantization technology that adapted to face feature changes and reduced feature size. In 2018, Wu et al 28 proposed a multibiological fusion authentication framework based on dynamic Bayesian decision‐making methods. The core idea was to use matching layer scores to help integrate biological characteristics at the decision‐making level.…”
Section: Related Workmentioning
confidence: 99%
“…In the literature, the studies based on biometric systems have shown that the use of several biometric methods will be necessary to obtain acceptable identification accuracy for an identification application of a large population of users [19]. In any case, it is not necessary for the different measurements to be mathematically combined.…”
Section: Basics and Access Controlmentioning
confidence: 99%